MATLAB based VHF and UHF amplitude scintillation characterization using the new low-latitude ionospheric tomography network (LITN) - Francisca, Dessy (Animo Repository, 2011)
Ionospheric scintillation has been studied intensively because it depreciates the satellite radio communication and navigational system performances. Scintillations are most severe at the equatorial anomaly region that corresponds to two belts, approximately 15oN and S of the magnetic equator. The Low-latitude Ionospheric Tomography Network (LITN) consists of ground stations extend at the northern latitude along ~120°E longitude. The LITN was established to focus on the equatorial anomaly dynamics. This study of the equatorial scintillation was achieved by examining the amplitude scintillation index S4. A computer application was designed to acquire and process data from the LITN to detect scintillation occurrences. Parameters such as amplitude scintillation index S4, elevation angle, satellite, date, time, receiver ground station, and geographical location are important for amplitude scintillation observation. Scintillation variations with operating frequency, local time, geographical location, solar and magnetic activity were observed. Ionospheric irregularity near the magnetic equator is associated with the Rayleigh-Taylor instability processes. Solar activity and magnetic activity result in the ionization and composition changes in the ionosphere.